A New Genus for Fabia Obtusidentata Dai, Feng, Song and Chen, 1980, a Pea Crab (Decapoda: Brachyura: Pinnotheridae) Symbiotic with the Moon Scallop AmusiumPleuronectes () (Mollusca: Pectinidae). Issue 5 (1st September 2016) - Ng, Peter K. L.; Ho, Ping-Ho
Abstract: The western Pacific pinnotherid crab, Fabia obtusidentata Dai, Feng, Song and Chen, 1980, which lives in the saucer scallop, Amusium (Pectinidae), is found not to belong to Fabia Dana, 1851 s. str. or Pinnotheres Bosc, 1802 . In contrast to these two genera, F. obtusidentata possesses a carapace not having longitudinal grooves, a third maxilliped in which the dactylus is slender and inserted one-third from the proximal end of the conical propodus, and a prominently elongated right third ambulatory leg with a long dactylus. It is here referred to its own genus, Amusiotheres gen. nov. Pinnotheres hanumantharaoi Devi and Shyamasundari, 1989, from India, is also transferred to the new genus.